Undersea fiber optic networks past, present, and future. - Kerfoot, F.W (IEEE Journal on selected areas in communications)
Undersea lightwave transmission systems have made tremendous progress in both capacity and network architecture since their introduction in the mid 1980s. Capacities have grown from 280 Mb/s in the first systems to 40 Gb/s or more for the fourth-generation systems being installed today using wavelength division multiplexing (WDM). Network architectures have progressed from simple point to point links to fully redundant rings and complex trunk and branch architectures. Both technology and market opportunities indicate that this rapid growth will extend well into the future